Chemical modifications of polyphenols for the development of new molecules foods for the treatment of metabolic disorders - Carullo, Gabriele; Andò, Sebastiano; Aiello, Francesca (Università della Calabria, 2020)
Metabolic disorders represent the principal cause of death in the industrialized world, affecting several people, because of their incorrect lifestyle. Among them, Type 2 Diabetes Mellitus and related comorbidities, such diabetic wounds, and hypertension represent the most studied examples of metabolism-associated diseases. In this context, the role of food-derived products and hybrid molecules has been investigated in this thesis. Two different braches have been investigated: one regarding food chemistry and one regarding medicinal chemistry. In food chemistry section, wine-making byproducts were used as starting point for the development of food ingredients able to modulate vascular tone in rat aortic rings. In particular, autochthonous (Calabria, southern Italy) white grape pomaces of Mantonico and Pecorello and red grape pomaces of Magliocco dolce (also known as Arvino) have been used. The pomaces were extracted in order to obtain samples, that were chemically-characterized and assayed in rat aorta rings. The results obtained and published demonstrated how these extracts were able to modulate vascular tone by a combination of antioxidant and nitric oxide-mediated effects; in the case of white pomaces, these effects were also assayed when the extract was embedded in a pectin matrix. In line with this, also a functional kefir was produced in order to evaluate its efficacy as anti-inflammatory agent for gastric epithelium, showing how the addition of the Sangiovese pomace extract was able to improve the activity of kefir. In medicinal chemistry section, the role of polyphenols, present in food products, was evaluated in order to drive their activity versus specific molecular pathways. In this field, we used quercetin, in combination with oleic acid, developing GPR40/FFA1 agonists that demonstrated to be useful insulin secretagogue agents. In particular, one derivative was also assayed in wound healing models, demonstrating the role of the receptor also in this proliferation process. In line with this, the GPR120/FFA4 demonstrated interesting pharmacological activities. Their agonists were able to modulate incretin secretion, with interesting anti-diabetic effect. Nevertheless, little structural determinants are present in literature. In this context, in my Spanish experience at University of Seville, I isolated (S)- pinocembrin from honey, and decided to create molecular hybrids, according to a homology model published. The hybrids obtained demonstrated a useful GPR120 agonist activity, promoting wound healing in HaCaT cell line. Furthermore, quercetin and morin were used as template for the development of new KCa1.1 and Cav1.2 channel modulators, with the aim of obtaining new suitable anti-hypertensive candidates. The results obtained showed how quercetin derivatives maintain their activity versus KCa1.1 channel, while morin derivatives demonstrated to activate KCa1.1 channel, behavior not registered in the case of parent compound. These results are now under review for publication.
Università sella Calabria. Dipartimento di Farmacia e Scienze della Salute e della Nutrizione Dottorato di Ricerca in Medicina traslazionale. Ciclo XXXII
Keywords: Biocatalysis; Waste management; Diabetes; Hypertension